2020
DOI: 10.1080/0886022x.2020.1818580
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin on busulfan-induced renal toxicity in male rats

Abstract: Aim: The aim of this study was to evaluate the effects of curcumin in an experimental model of busulfan-induced renal toxicity with emphasis on importance of histological alterations. Methods: In this study, we utilized 32 adult male Wistar rats (250 ± 10 g). All the animals were divided into four experimental groups randomly: (I) Control; (II) Busulfan (40 mg/kg); (III) Olive oil; and (IV) Curcumin (80 mg/kg/day). Finally, the rats were euthanized and kidney tissues were taken for histopathology experiments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…However, its side effects have become increasingly evident with its widespread use. Numerous studies have shown that it is highly carcinogenic and teratogenic and can severely affect the functioning of body organs such as the gonads and the central nervous system [4]. In clinical practice, busulfan is often used in combination with cyclophospha mide or fludarabine [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, its side effects have become increasingly evident with its widespread use. Numerous studies have shown that it is highly carcinogenic and teratogenic and can severely affect the functioning of body organs such as the gonads and the central nervous system [4]. In clinical practice, busulfan is often used in combination with cyclophospha mide or fludarabine [5].…”
Section: Introductionmentioning
confidence: 99%